Paysage de Fantasy... : la rédemption et l’errance dans "Fullmetal Alchemist" - CASTA, Isabelle Rachel (Ondina - Ondine, 2019)
Any critical commentary on Fullmetal Alchemist leans against the enormous vibrating body-canvas of a work with multiple media, with almost infinite ramifications, the archetype of the "mainstream" youth culture. The fact remains that at the heart of the stories snakes the thread - the great Path that each person must follow, from birth to death, then from death to salvation; in the "unexpected journey" it is indeed no return, the journey being exerted within its own psyche at least as much as crossing the worlds - or times - in the great upheaval of fantasy. It is the initiatory journey of two brothers, Edward and Alphonse Elric, who seems the richest in interpretations: having tried to bring back their mother to life by a failed alchemical operation, they lose their bodily integrity ... but do not die ; they leave, they travel, they make their memory a secret time, a revolt. Their quest resembles the bottom of ours, it is exemplary: one day or the other, we must dismount and accept the law of others, before the watchers do sign, the night is over, and that the meaning flows. Keywords: alchemy; resurrection; brotherhood; dystopia; fantasy